Targeting ErbB3: the New RTK(id) on the Prostate Cancer Block - K. Jathal, Maitreyee; Chen, Liqun; Mudryj, Maria; M. Ghosh, Paramita (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Most prostate cancers (PCa) are critically reliant on functional androgen receptor (AR) signaling. At its onset, PCa is androgen-dependent and although temporarily halted by surgically or pharmacologically blocking the AR (androgen ablation), the disease ultimately recurs as an aggressive, fatal castration resistant prostate cancer (CRPC). FDAapproved treatments like docetaxel, a chemotherapeutic agent, and Provenge, a cancer vaccine, extend survival by a scant 3 and 4 months, respectively. It is clear that more effective drugs targeting CRPC are urgently needed. The ErbB family (EGFR/ErbB1, ErbB2/HER2/neu, ErbB3/HER3 and ErbB4/HER4) of receptor tyrosine kinases (RTKs) have long been implicated in PCa initiation and progression, but inhibitors of ErbB1 and ErbB2 (prototypic family members) fared poorly in PCa clinical trials. Recent research suggests that another family member ErbB3 abets emergence of the castrationresistant phenotype. Considerable efforts are being directed towards understanding ErbB3-mediated molecular mechanisms of castration resistance and searching for novel ways of inhibiting ErbB3 activity via rational drug design. Antibody- based therapy that prevents ligand binding to ErbB3 appears promising and fully-humanized antibodies that inhibit ligand-induced phosphorylation of ErbB3 are currently in early development. Small molecule tyrosine kinase inhibitors are also being vigorously pursued, as are siRNA-based approaches and combination treatment strategies- the simultaneous suppression of ErbB3 and its signaling partners or downstream effectors - with the primary purpose of undermining the resiliency of ErbB3-mediated signal transduction. This review summarizes the existing literature and reinforces the importance of ErbB3 as a therapeutic target in the clinical management of prostate cancer.
Keywords: ErbB3